2020
DOI: 10.1111/hiv.13010
|View full text |Cite
|
Sign up to set email alerts
|

Is contact between men who have sex with men and non‐governmental organizations providing harm reduction associated with improved HIV outcomes?

Abstract: Objectives There is a high prevalence of HIV (5.2% in 2018) among men who have sex with men (MSM) in Ukraine. HIV testing, condom provision and facilitated linkage to HIV treatment have been funded by various bodies through non‐governmental organizations (NGOs). We investigated whether contact with these NGOs was associated with improved prevention and treatment outcomes among MSM in Ukraine. Methods Data were taken from four rounds of integrated bio‐behavioural surveys among MSM in Ukraine (2011, N = 5950; 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…There has been limited research on Ukraine’s HIV epidemic among MSM. Our previous study used in this analysis found that NGOs were associated with beneficial outcomes among MSM( 10 ), agreeing with other research( 35 ). An MSM modelling study in Poland found that immediate initiation of HIV treatment was cost-saving from the public perspective( 36 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There has been limited research on Ukraine’s HIV epidemic among MSM. Our previous study used in this analysis found that NGOs were associated with beneficial outcomes among MSM( 10 ), agreeing with other research( 35 ). An MSM modelling study in Poland found that immediate initiation of HIV treatment was cost-saving from the public perspective( 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…MSM become clients of NGOs at time-varying rates from 2003 and cease contact with NGOs at a constant rate. HIV-positive MSM become NGO clients at a higher rate due to NGO efforts to link HIV-positive MSM to care; our previous analyses show a higher proportion of NGO clients are HIV-positive than for non-NGO clients( 10 ).…”
Section: Methodsmentioning
confidence: 74%
See 3 more Smart Citations